3-Cyclohexylsulfinyl-5-iodo-2-methyl-1-benzofuran - Choi, Hong Dae (International Union of Crystallography, 2011)
There are two independent molecules, A and B, in the asymmetric unit of the title compound, C(15)H(17)ClO(2)S, in each of which the cyclohexyl ring adopts a chair conformation. The benzofuran units in each molecule are essentially planar, with mean deviations from a least-squares plane defined by the nine constituent ring atoms of 0.006 (2) Å for A and 0.011 (2) Å for B. In the crystal, molecules are linked by weak intermolecular C—H⋯O and C—H⋯π interactions and by two I⋯O contacts [I⋯O = 3.079 (2) and 3.017 (2) Å].